2012
DOI: 10.1249/mss.0b013e318257d2db
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Training Reduces CD8+ T-cell Redistribution in Response to Exercise

Abstract: High-intensity training impaired CD8(+)TL mobilization and egress in response to exercise. Highly cytotoxic CD8(+)TLs were primarily responsible for the reduced mobilization of CD8(+)TLs, which occurred in parallel with smaller neuroendocrine responses. The reduced capacity for CD8(+)TLs to leave blood after exercise with high-intensity training was accounted for primarily by naive, and also, highly cytotoxic CD8(+)TLs. This impaired CD8(+)TL redistribution in athletes undertaking intensified training may impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 37 publications
4
46
0
1
Order By: Relevance
“…Acute exercise is well known to stimulate the redistribution of T cells into the circulation in humans (Simpson et al 2007;Turner et al 2010;Witard et al 2012). Most previous studies have used a controlled exercise bout (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Acute exercise is well known to stimulate the redistribution of T cells into the circulation in humans (Simpson et al 2007;Turner et al 2010;Witard et al 2012). Most previous studies have used a controlled exercise bout (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Witard et al (22) observed a reduction in CD8 + cells in response to intense exercise, demonstrating that the lymphocyte profile is highly sensitive to exercise and is largely driven by CD8 + T cells. However, different from our study, Witard et al (22) examined young adults and the acute effect of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Witard et al (22) observed a reduction in CD8 + cells in response to intense exercise, demonstrating that the lymphocyte profile is highly sensitive to exercise and is largely driven by CD8 + T cells. However, different from our study, Witard et al (22) examined young adults and the acute effect of exercise. Recently, Brown et al (32) highlighted the importance of gender and training status for the redistribution of senescent and naive T lymphocytes in response to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein it is known that fish oil can improve immune function in the recovery period after exercise [13], suggesting that fish oil supplementation may reduce URTI incidence although, as with vitamin D, there are no studies investigating this at present. One method which has successfully been shown to reduce URTI incidence is through an increase in dietary protein intake [29]. In this study, with a counterbalanced design, participants carried out 7 days of high intensity exercise training on either a normal (1.5g/kg body mass/day) or high protein diet (3.0g/kg body mass/day).…”
Section: Introductionmentioning
confidence: 99%